Performance of Structural Lightweight Concrete containing Metakaolin after Elevated Temperature - Demirel, Bahar; Gultekin, Ezgi; Alyamac, Kursat Esat (Korean Society of Civil Engineers-Ksce, 2019)
The aim of the current research is to determine the multiple influences of the amount of metakaolin and high temperature on the compressive strength of structural lightweight concrete (SLWC) applying response surface method (RSM). For this purpose, the lightweight concrete specimens were produced by pumice sand, and metakaolin replacing with cement at different ratios. The unit weight of hardened concrete, 28-day compressive strength, elevated temperature, ultrasonic pulse velocity, and sorptivity tests were performed. Moreover, then, two variables defined as the elevated temperature of 20, 400, 600, and 800 degrees C, and the metakaolin-to-cement ratio of 0%, 5%, 11%, 18%, and 25%, to obtain the compressive strength of structural lightweight concrete. The effects of each variable on the response which is the compressive strength were determined following the ANOVA (analysis of variation) analysis, and the equation of the model was developed. Eventually, the developed equation could be utilized to estimate the compressive strength of the structural lightweight concrete for requested values of each variable.
Keywords: structural lightweight concrete; pumice sand; metakaolin; elevated temperature; compressive strength; response surface method